Thyroglossal Duct Cyst Carcinoma in a Young Female: Case Report and Review of Literature. (31st July 2019) - Van Beck, Jenna; Khaja, Sobia F.
Abstract : Thyroglossal duct remnants form during embryologic development and can develop into a thyroglossal duct cyst (TGDC). In rare cases, carcinoma is present within these cysts, most commonly papillary thyroid carcinoma. Diagnosis is difficult, but imaging and fine-needle aspiration (FNA) biopsies can help with the diagnosis. Given the rarity of TGDC carcinoma, treatment is not well agreed upon and can include the Sistrunk procedure, thyroidectomy, nodal dissection, and postoperative radioactive iodine treatment. Here, we describe the presentation, workup, and treatment of a 20-year-old female with papillary thyroid carcinoma present within both a thyroglossal duct cyst and the thyroid gland.